Dos pioneiros do MST às políticas educacionais do campo : uma narrativa a partir da ocupação da Fazenda Annoni - Lauer, Munir José (2021)
This Thesis narrates, under the historical subject standpoint, the process of influence of the Landless Rural Workers Movement (MST) in the construction/creation of the educational policies of the Field. Hence, it investigates, indicates, and interprets the signs of the presence and influence of MST on the establishment of current educational policies of the Field. Considering a starting point the occupation of the former Annoni Farm on October 29, 1985, in the city of Pontão, RS, Brazil, the present study, supported by the historical and dialectical method, evidences the hypothesis that the existing educational policies of the Field are priority results of the movements and processes triggered by the MST, since the occupation of the Annoni Farm. Placing the investigative context between 1985 and 2018, the theoretical logic of this investigation is primarily based on the aspect of the subjects and later the collective organization. This thesis starts from a micro scenario of the subjects from the Annoni Farm and primary formative experiences, and gradually advances to a macro scenario of the formative processes while belonging to a social organization of the masses, education in/of MST, and educational policies of the Field. It is intended, from the beginning, to establish a time and chronological line of the facts - of subjects, collective organization, formation, education, and educational policies of the Field. The research is qualitative and characterized as bibliographical/documentary, presenting traces of an autobiographical study. Specifically, the study describes the pioneers who participated in the occupation of the Annoni Farm, as well as the formative process of leadership in this historical fact. The study shows how the formative experiences of landless farmers at the Annoni camp were from the base centers, passing through the influence of the Christian faith, up to the subjective and collective formative process of (re)construction of the social identity. The thesis measures the conflicts of interest of landless farmers during the disruption process of the main camp up to the definite settlement, discusses primary educational experiences developed at the camp that resulted in the current schools, describes the process of identity formation of landless farmers into Landless Farmers, and explains education in/of the Landless Movement and its direct relationship with the educational policies of the Field. Lastly, it addresses the public policy and education in/of MST. It is concluded that Education of the Field is directly mediated by the MST. There are two assertions for this affirmation. The first explanation is completely inherent to the formative and educational processes promoted by the MST in their practices. This agrees with both the entire path started in the first year of the Annoni Farm camp and the primary education experiences later implemented in the schools of settlements across Brazil. The second explanation mentions the specific trajectory (of organization and training) of the school educational work of the MST, in a national chronological view that is noticed in documents. In this context, 12 policies and 33 documents stand out. It is exactly in these two aspects - the creation of policies and the documents - that are found signs of the presence and the influence of MST on the establishment of the current educational policies of the Field.